2010
DOI: 10.4049/jimmunol.0902621
|View full text |Cite
|
Sign up to set email alerts
|

HIV Protective KIR3DL1 and HLA-B Genotypes Influence NK Cell Function Following Stimulation with HLA-Devoid Cells

Abstract: Material Supplementary 1.DC1http://www.jimmunol.org/content/suppl/2010/01/08/jimmunol.090262

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 57 publications
6
94
0
Order By: Relevance
“…This possibility is concordant with the epidemiological observation that SPs have higher frequencies of inhibitory KIR3DL1/HLA-Bw4 ligand combinations than do individuals with more rapidly progressing infections (45). It was demonstrated that these KIR/HLA combinations increase the functional potential of NK cells during the ontological process of NK cell education (46,47) and that this education results in higher anti-HIV ADCC against autologous targets (48). Furthermore, an additional study (49) demonstrated that NK cells carrying KIR3DL1 are expanded in primary HIV infection.…”
Section: Discussionsupporting
confidence: 75%
“…This possibility is concordant with the epidemiological observation that SPs have higher frequencies of inhibitory KIR3DL1/HLA-Bw4 ligand combinations than do individuals with more rapidly progressing infections (45). It was demonstrated that these KIR/HLA combinations increase the functional potential of NK cells during the ontological process of NK cell education (46,47) and that this education results in higher anti-HIV ADCC against autologous targets (48). Furthermore, an additional study (49) demonstrated that NK cells carrying KIR3DL1 are expanded in primary HIV infection.…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, changes in the environment in various disease settings result in the recruitment of specific NK cell subsets, allowing for greater disease control among certain patients (30,(35)(36)(37)(38). In AHCT for neuroblastoma, the presence of a "missing ligand" for inhibitory KIR was associated with improved survival, suggesting that normally hyporesponsive unlicensed NK cells are specifically recruited to control disease in this setting (39).…”
mentioning
confidence: 99%
“…The functional potential of 46 SP stimulated with HLA-devoid K562 cells was assessed as previously described [4]. Briefly, cryopreserved PBMC were thawed and resuspended at 10 6 cells/ml in RPMI 1640 that contained 10% FBS, 2mM L-glutamine, 50 IU penicillin and 50µg/ml streptomycin (cRPMI) (all from Wisent).…”
Section: Nk Cell Activationmentioning
confidence: 99%
“…All subjects were HLA typed as previously described (4). KIR3DS/L1 genotyping was performed by PCR with 2 sets of sequence-specific primers (PCR-SSP) as previously described [4].…”
Section: Mhc and Kir Genotypingmentioning
confidence: 99%
See 1 more Smart Citation